Vortex evolution within propeller induced scour hole around a vertical quay wall - Wei, Maoxing (2020)
This paper presents an experimental study on the characteristics of the propeller-induced flow field and its associated scour hole around a closed type quay (with a vertical quay wall). An "oblique particle image velocimetry" (OPIV) technique, which allows a concurrent measurement of the velocity field and scour profile, was employed in measuring the streamwise flow field (jet central plane) and the longitudinal centerline scour profile. The asymptotic scour profiles obtained in this study were compared with that induced by an unconfined propeller jet in the absence of any berthing structure, which demonstrates the critical role of the presence of the quay wall as an obstacle in shaping the scour profile under the condition of different wall clearances (i.e., longitudinal distance between propeller and wall). Moreover, by comparing the vortical structure within the asymptotic scour hole around the vertical quay wall with its counterpart in the case of an open quay (with a slope quay wall), the paper examines the effect of quay types on the formation of the vortex system and how it determines the geometrical characteristic of the final scour profile. Furthermore, the temporal development of the mean vorticity field and the vortex system are discussed in terms of their implications on the evolution of the scour hole. In particular, comparison of the circulation development of the observed vortices allows a better understanding of the vortex scouring mechanism. Energy spectra analysis reveals that at the vortex centers, their energy spectra distributions consistently follow the -5/3 law throughout the entire scouring process. As the scour process evolves, the turbulent energy associated with the near-bed vortex, which is responsible for scouring, is gradually reduced, especially for the small-scale eddies, indicating a contribution of the dissipated turbulent energy in excavating the scour hole. Finally, a comparison of the near-bed flow characteristics of the average kinetic energy (AKE), turbulent kinetic energy (TKE), and Reynolds shear stress (RSS) are also discussed in terms of their implications for the scour hole development.